The Effectiveness of the Drug Free Program (Bersinar) by the National Narcotics Agency of Palu City in Relation to Family Resilience - Tazkia Aulia; Taufan, Taufan; Siti Musyahidah (State Islamic University Datokarama Palu, 2025)
This research aims to evaluate the effectiveness of the Drug Free Program or “bersinar” conducted by the National Narcotics Board of Palu City in addressing family resilience dysfunction and to analyze these efforts from the perspective of Maqashid Syariah. Using a qualitative empirical approach with descriptive analysis this study gathers data through in depth interviews observations and documentation involving various stakeholders in Palu City. The results indicate that the “bersinar” program has not yet achieved optimal effectiveness in overcoming family resilience dysfunction due to several inhibiting factors such as inconsistent coordination between agencies limited budget for rehabilitation services and low community participation caused by social stigma. Furthermore many families of drug users exhibit structural and functional disturbances including poor communication and lack of emotional support which hinder the recovery process of addicts. From the perspective of Maqashid Syariah the success of narcotics prevention is deeply rooted in the protection of the five essential elements especially the soul and the intellect which can only be achieved if family resilience is functioning optimally as the primary social defense.